Autotematyzm out of the blue. Kilka uwag o poezji Julii Hartwig na marginesie wiersza Reprymenda - Grądziel-Wójcik, Joanna (Przestrzenie Teorii, 2023)
The article discusses different variants of metareflection in Julia Hartwig’s poetry, situating them against the background of a comprehensive concept of the poet’s work. The analysis of her poem Reprymenda [Reprimand] gives rise to a proposal of authotematism specific to Hartwig’s poetry, here called ‘out of the blue’ autothematism and contrasted with the concept of avant-garde poetry. This metapoetic formula is then extended to other texts in the volume Jasne niejasne [Bright Unclear], in which the mimetic aspect of literature in particular is problematised and the ethical dimension of Hartwig’s oeuvre is highlighted.